2023
DOI: 10.1002/cam4.6475
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 evaluation of the safety and tolerability of niraparib in combination with everolimus in advanced ovarian and breast cancers

David Starks,
Luis Rojas‐Espaillat,
Tobias Meissner
et al.

Abstract: ObjectivesPhase 1 trial to determine the safety and tolerability of everolimus and niraparib in patients with advanced ovarian and breast malignancies.ResultsFourteen heavily pretreated patients were enrolled (12 high‐grade serous ovarian cancer, 1 clear cell ovarian cancer, and 1 triple negative breast cancer). All patients were PARP naïve and received comprehensive genomic profiling prior to enrollment. Two DLTs were experienced in cohort 2 (niraparib 200 mg daily and everolimus 5 mg 3 days per week) with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Furthermore, a phase 1 trial to determine the safety and tolerability of everolimus in combination with PARP inhibitor (PARPi) niraparib in patients with advanced ovarian or breast cancer was previously reported. This study demonstrated that the combination of everolimus and niraparib was associated with significant toxicity, even at lower doses of both agents, and was therefore not feasible; no TSC2 mutations were identified in any of the patients in that study ( 15 ).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, a phase 1 trial to determine the safety and tolerability of everolimus in combination with PARP inhibitor (PARPi) niraparib in patients with advanced ovarian or breast cancer was previously reported. This study demonstrated that the combination of everolimus and niraparib was associated with significant toxicity, even at lower doses of both agents, and was therefore not feasible; no TSC2 mutations were identified in any of the patients in that study ( 15 ).…”
Section: Discussionmentioning
confidence: 87%